A Comparative Study of Tolerability of Losartan versus Atenolol in Essential Hypertension and Their Effect on Lipid Profile - Amrutha Torvi; Prashanth D; Soujanya S; Lingraj Patil (Universitas Padjadjaran, Indonesia, 2021)
Hypertension is a vascular disease entity that is a common problem occurring worldwide, characterized by sustained elevated blood pressure. Losartan and atenolol are two medications that are commonly used in hypertensive patients. However, the mechanism of tolerability their effect on lipid profile is not clearly described. Thus, the aims of this study were to study the tolerability of losartan with atenolol in patients with hypertension and the changes in lipid profile on treatment. This research was a prospective, open-label, parallel-group, comparative study conducted in the medicine out-patient department (OPD), where 100 patients aged 40-60 years with newly diagnosed mild and moderate hypertension. We classified patients randomly into two groups, losartan, and atenolol (50 patients of each). Patients were recruited for a period of 6 months and were called for follow-up visits at the third and sixth months. In this study mean age of the patients was 52.72 years. Our study observed that baseline systolic (P=0.704), as well as diastolic blood pressure (BP) (P=0.324), was comparable between both groups. Both systolic (P=0.125), as well as diastolic BP (P=0.108) at 6-months, was comparable between both groups. It was observed that mean total cholesterol levels were comparable between both groups at baseline (P=0.665). Moreover, adverse effects were observed more commonly in group atenolol, headache being the most common followed by dizziness and palpitation. Our study observed that both losartan and atenolol are equally effective in long- term reduction of blood pressure. Additionally, losartan also significantly improved lipid profile.